Disability and international development : a guide for students and practitioners - Cobley, David (Routledge; London, 2018)
"Despite growing evidence of a close and complex relationship between disability and poverty, development policy, planning and programming has often failed to take full account of the concerns of disabled people. However, following the 2006 UN Convention on the Rights of Persons with Disabilities and the post-2015 sustainable development agenda, which promises to 'leave no one behind', there have been increasing calls from governments and development agencies for disability to be mainstreamed into all development planning. Disability and International Development provides a comprehensive overview of key themes in the field of disability and development, including issues around identity, poverty, disability rights, education, health, livelihoods, disaster recovery and approaches to researching disability. The book engages with relevant theory and draws on existing literature in the field, as well as the author's own research and teaching experience, to explore key issues using a range of examples taken from around the world. Written in an accessible and engaging style to suit both students and practitioners, the book also includes a wide range of reflection exercises, discussion questions and further reading suggestions, making it the perfect introduction to disability and international development"--
Includes bibliographical references.
Keywords: People with disabilities -- Services for -- International cooperation; People with disabilities -- Government policy -- International cooperation